Epizoic Diatom Community Structure in Snails Cerithidea obtusa and Nerita articulata in the Mangrove Ecosystem, Dumai City, Riau Province - Renata, Vivien; Siregar, Sofyan Husein; Efriyeldi, Efriyeldi (Jurnal Perikanan dan Kelautan, 2023)
The purpose of this study was to determine the type, abundance, and community structure of epizoic diatoms attached to the shells of the snails Cerithidea obtusa and Nerita articulata in the mangrove ecosystem of Dumai City, Riau Province. This research was conducted in January 2022. A sampling of snail shells took place in the mangrove ecosystem of the city of Dumai, Riau Province, and was identified at the Marine Chemistry Laboratory, Department of Marine Science, Faculty of Fisheries and Marine, Universitas Riau. Based on the research that has been done, the results show that there are 13 genera of epizoic diatoms consisting of 5 genera centrales and 8 genera of pennales order. The highest abundance of epizoic diatoms in C.obtusa snail shells was at station II with a value of 29,687 ind/cm2. While the highest abundance of epizoic diatoms in N.articulata shells was at station I. Based on the average values ​​​​of diversity index (H'), dominance index (D), and uniformity index (E) it can be concluded that epizoic diatoms in C.obtusa and N.articulata have a moderate biota community balance value, moderate polluted water quality, no dominant species and unbalanced organism uniformity and food competition occurs.